Pengembangan Media Pembelajaran Berbasis Metode Montessori pada Pembelajaran IPA Siswa Kelas V di SDN Rama II Kota Tangerang - Aisah Nur Fitri; Rizki Zuliani; Candra Puspita Rini (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Learning media are learning aids that can be physical or non-physical to convey messages from teachers to students. The purpose of this study is to determine the effectiveness of the use and process of product development in the form of Montessori-based learning media in science learning for fifth grade students. The research is a development research (R & D) with the Sugiyono development procedure. Based on the result of product validation, it received an “appropriate” assessment with a score of 3,6 from material experts. While media experts rated “strongly agree” with a score of 4,5. Based on result of product trials, it is known that average pretest value is 52,64 and posttest is 76,66 so that it has increased. Product assessment by students through questionnaires gets a score of 3,98 or when views in the classification table, namely “agree”. Based on the use trial, the average pretest value was 36,8 and posttest was 72,2 so thatit experienced an increase. Product assessment by students through questionnaires gets an average score of 4,3 or if seen in the table, it is “Strongly agree”. This shows that the learning media based on the Montessori method development can be said to be feasible to use.